If you had my love - Lopez, Jennifer; Jenkins, Rodney; Sony Music Entertainment (California : Sony Music Entertainment, 1999)
Contains four pop tracks taken from the album On The 6.
CD 1 : Radio edit -- Pablo Flores remix -- Dark Child remix -- Album version.
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Popular music -- 1991-2000.